(untitled) (Research, Society and Development, 2024)
Study Design: Case Report. Oronasal communication can be a result of congenital disorders, pathological lesions, or inadequate treatment. It consists of abnormal communication between the nasal and oral cavities. Objective: This paper aims to present a case report of a female patient who intended for dental implants but was referred to the maxillofacial surgery department presenting a cone beam computed tomography with incidental finding in the anterior part of the maxilla. Methods: The first surgical procedure consisted of the resection of the lesion associated with bone graft with buccal fat pad flap and posterior histopathological study. After three months the patient developed an oronasal fistula. During the second surgical management, the authors chose platelet concentrates (L-PRF) to fill the bone defects associated with the palatal flap. Results: After one year of follow-up, the patient presented definitive soft tissue healing, no exposure of bone tissue, and the closure of oronasal communication. The new CT scan and panoramic x-ray showed satisfactory bone healing. Conclusion: The present study demonstrated the association of L-PRF with xenograft and palatal flap can be a viable method for the management of patients with oronasal fistula. This report adheres to the SCARE guidelines for the reporting of surgical cases in medical literature.